Contributions of Muslim mathematicians to the invention of analysis: The concepts of limit and infinity in the works of Thabit Ibn Qurra as a model - ouakid, Abdul Hadi; temar, nadji; aitmokhtar, ahmed (The Algerian Historical Journal, 2026)
This study aims to show the contributions of Muslim mathematicians that led to the invention of analysis. Although mathematics historians acknowledge Muslim mathematicians in developing geometry and inventing algebra, they attribute all the credit for inventing mathematical analysis to the Europeans. Mathematics in Islamic civilization began with the acquisition from previous nations, followed by a period of creativity with great development in geometry and the invention of algebra. These two sciences were the main reason for the birth of analysis after being inherited directly by the Europeans from Muslim scholars. Modern analysis studies infinity quantities based on the limit concept, which has its roots in the geometric “method of exhaustion”. However, the works of Thabit Ibn Qurra in the ninth century AD included the concepts of limit and infinity by adding algebraic calculation to this method.